Factors Determining Buying Behaviour of Customers towards Life Insurance Products in Karnataka - Varughese, Jijo Shaji (Journal of Global Economy, Business and Finance, 2025)
Insurance sector in India plays a dynamic role in the development of its economy. It provides the opportunities for savings amongst the individuals, safeguards their future and helps the insurance sector form a massive pool of funds which can be further utilized. Therefore, insurance companies have found an essential task to understand what makes the customers to buy insurance products. The purpose of this research is to find out the factors determining buying behaviour of customers towards life insurance products in Karnataka. With help of SPSS, regression analysis was done to find out influence of personal, social, marketing and economic factors on buying behaviour of customers towards life insurance products in Karnataka. Structure questionnaires was designed to collect the required data from the 263 selected policy holders in the various districts of Karnataka. The results of the study showed that, personal, social factors such as reference groups, insurance agent, social media, communications and technology, friends and family, exposure to risk, previous experience has significant relationship with customer buying behaviour towards insurance products. The marketing factors such as service quality, well informed (knowledge of insurance), accessibility of insurance products, (place) company’s effective promotional strategies, customer loyalty has positive association with customer buying behaviour towards insurance products. It also identified that, economic factors such as products found value for money, low switching cost, demand for the insurance produces, company’s competition advantages to customers, risk coverage, tax benefits, cost of healthcare are the main determinant factors for the customer buying behaviour towards insurance products.